2021
DOI: 10.1186/s40562-020-00172-6
|View full text |Cite
|
Sign up to set email alerts
|

Accessing future crop yield and crop water productivity over the Heihe River basin in northwest China under a changing climate

Abstract: Quantitative evaluation of the response of crop yield and crop water productivity (CWP) to future climate change is important to prevent or mitigate the adverse effects of climate change. This study made such an evaluation for the agricultural land over the Heihe River basin in northwest China. The ability of 31 climate models for simulating the precipitation, maximum temperature, and minimum temperature was evaluated for the studied area, and a multi-model ensemble was employed. Using the previously well-esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…In addition to research on the response of crop yields to climate change based on historical observation data, process-based crop models were also used in many studies to predict crop yield changes under different climate change scenarios. 19,20 To separate the composite effects of climate change and agricultural practice, first-order difference multiple regression has empirical advantages. 21 Under the assumption that the technical level progressed evenly, historical data can be used for first-order difference multiple regression to capture the effects of key factors on crops, which also facilitates research on climate-crop yield relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to research on the response of crop yields to climate change based on historical observation data, process-based crop models were also used in many studies to predict crop yield changes under different climate change scenarios. 19,20 To separate the composite effects of climate change and agricultural practice, first-order difference multiple regression has empirical advantages. 21 Under the assumption that the technical level progressed evenly, historical data can be used for first-order difference multiple regression to capture the effects of key factors on crops, which also facilitates research on climate-crop yield relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Sabella et al (2020) indicated that the plant life cycle was clearly shorter under climate change due to the physiological strategy of the plant to escape the high summer temperatures through the early ripening of the kernels. In addition, Liu et al (2021) revealed that the impacts of future climate change on crop yield and CWP of wheat, barley and canola would all be negative.…”
Section: Crop Water Productivitymentioning
confidence: 99%
“…Croplands are mainly located in the upstream and middle stream in the Heihe River Basin with an area of about 8.5 × 10 5 ha [27]. The Heihe River Basin is suitable for wheat, corn and Polish canola, with an annual output of 9.9 × 10 5 tons [28]. The total area of forest is about 1.8 × 10 5 ha [28], which is mainly located in the southwest of this region.…”
Section: Study Areamentioning
confidence: 99%
“…The Heihe River Basin is suitable for wheat, corn and Polish canola, with an annual output of 9.9 × 10 5 tons [28]. The total area of forest is about 1.8 × 10 5 ha [28], which is mainly located in the southwest of this region. The Heihe River Basin is a typical inland river basin in China, where water-stressed ecosystems are widely distributed, the eco-hydrological processes are complex, and the environment is more sensitive to climate change.…”
Section: Study Areamentioning
confidence: 99%